PROFITABILITY: THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY AND CORPORATE GOVERNANCE IMPLEMENTATION (International Journal of Innovative Technologies in Economy, 2022)
The purpose of this observation is first, to determine the impact of Corporate Social Responsibility (CSR) implementation on the profitability of banking corporates registered on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The second is to determine the impact of Corporate Governance (CG) implementation on the profitability of banking corporates registered on the IDX in the 2017-2021 period. The sampling method is purposive sampling. Based on the results of the observation, it can be conducted that CSR has no significant effect on profitability, while CG with the indicators of institutional ownership, managerial ownership, board of commissioners, board of directors, and audit committee has a significant positive effect on profitability.